Determinan Kepatuhan Wajib Pajak UMKM Pasca Penerapan Peraturan Pemerintah No. 23 Tahun 2018 (Studi Kasus Pada UMKM yang Terdaftar di KPP Pratama Malang Utara) - Vinna Anggraeni; M. Cholid Mawardi; Umi Nandiroh (e_Jurnal Ilmiah Riset Akuntansi, 2023)
Micro, Small and Medium Enterprises (MSMEs) are a very important pillar in the economy in Indonesia. MSMEs play a very important role in tax revenue which is the main source of state revenue which has a very large role and is relied upon for the country's development, especially in Indonesia. This study aims to determine the effect of accounting understanding, tax understanding, taxpayer compliance costs on MSME taxpayer compliance. The population of this research is MSME taxpayers who are registered at KPP Pratama North Malang. This study used a purposive sampling technique for sampling. A total of 95 questionnaire data were obtained and processed with SPSS 29.0 for windows. The results of this study indicate that understanding of accounting has no effect on taxpayer compliance, understanding of taxation has a significant positive effect on taxpayer compliance, and the cost of taxpayer compliance has a significant negative effect on MSME taxpayer compliance.Keyword: MSMEs, accounting understanding, tax understanding, tax compliance costs